The Effects of Adopting a Value Added Tax on Firms - David R. Agrawal; Laura V. Zimmermann (CESifo GmbH, 2024)
This paper studies the effects of transitioning from a system of sales taxes to a value-added tax (VAT) on firm-level outcomes. We construct a dataset of product- and state-specific tax rates before and after India gradually switched from a sales tax to a VAT. Exploiting staggered state-level adoptions, we first show that following the transition, effective tax rates declined substantially and complexity as measured by various proxies generally also fell. We then show that sales increased by 57% in the medium run. The reform resulted in increased earnings for workers and higher amounts of capital and digital accounting.
Keywords: H21; H25; H26; H71; O17; O23; 330; value added tax; sales tax; production efficiency; firms